Determination of malnutrition risk in paediatrics patients with two screening tools: Is PYMS or STRONGkids effective? Is PYMS or STRONGkids effective? - Başmısırlı, Eda; Şahin, Habibe; Soylu, Meltem; İnanç, Neriman; Kendirci, Mustafa (Progress in Nutrition, 2022)
Early diagnosis of malnutrition is important in hospitalized children. Since the effectiveness of screening tools is still unclear, this study was conducted to assess the risk of malnutrition with PYMS and STRONGkids in inpatients children and to compare them with anthropometric measurements. In this cross-sectional study, the risk of malnutrition was determined by PYMS and STRONGkids in 222 patients aged from 1 to 16 years old. According to the BMI values of the patients, 84.7% were normal and 15.3% were acute malnourished. Severe and moderate stunting was detected in 8.1% and in 11.3% of chronic malnourished patients respectively. In patients without acute malnutrition, the lower malnutrition risk was found in 55.0% of the patients with PYMS whereas in 42.9% with STRONGkids. The detection rate of the moderate risk with STRONGkids (47.1%) was higher than PYMS (22.2%).In patients with acute malnutrition, PYMS could not detect low and moderate malnutrition risk. The detection rates with STRONGkids were 6.1% for low and 36.4% for moderate risk. STRONGkids' ability to detect patients with high malnutrition risk was lower (58.3%) than that of PMYS (100%). According to anthropometric measurements, PYMS was superior for detecting acute malnutrition while STRONGkids was superior for detecting chronic malnutrition.